Kualitas Jaringan Lokas Akses Fiber Optik pada Indihome PT. Telkom di Daerah Jimbaran - paramarta, gung eka; Sukadarmika, Gede; Sudiarta, Pande Ketut (Majalah Ilmiah Teknologi Elektro, 2016)
Abstract — In Indihome services can result in measurements and calculations will be compared with existing standardization . Analysis performed on the quality of the network , namely Rx Power ranges from -15 dBm up to -24 dBm . For attenuation value varies between 17 dB to 28 dB . Measurement of Internet services to customers obtained datarate of 10.6 Mbps , while the calculation for voice service needs and useetv each requiring 81.98 Kbps and 3.096 Mbps as the required services dipelanggan total 13.777 Mbps . Indihome very adequate availability of services , because it is provided downstream attainable rate of 2.3 Gbps up to 2.4 Gbps.
Keywords: Kualitas Jaringan, Voice, Internet, Useetv